Gut microbiome-mediated mechanisms in aging-related diseases: are probiotics ready for prime time? - Ren, Jing; Li, Huimin; Zeng, Guixing; Pang, Boxian; Wang, Qiuhong; Wei, Junping (Frontiers in Pharmacology, 2023)
Chronic low-grade inflammation exerts negative effects on health and is associated with aging and age-related diseases. Dysregulation of the gut flora is an important trigger of chronic low-grade inflammation. Changes in the composition of the gut flora and exposure to related metabolites interact with the inflammatory system of the host. This results in the development of crosstalk between the gut barrier and systemic immune system, contributing to chronic low-grade inflammation and impairment of health and aging-related well-being. Probiotics can increase the diversity of gut microbiota, protect the gut barrier, and regulate gut immunity, thereby reducing inflammation. Therefore, the use of probiotics is a promising strategy for the promotion of beneficial immunomodulation and protection of the gut barrier through gut microbiota. These processes may exert beneficial effects on inflammatory-derived diseases, which are common in the elderly.